Near Terahertz Silicon Conductivity Measurements via High-Q Resonant Cavity - Katz, Sarah (My University, 2010)
The electrical properties of many materials are not well characterized at frequencies in the near Terahertz regime. As the applications of Terahertz radiation are multiplying, the lack of a good model for the behavior of both dielectrics and conductors is a problem. To address this, a computational model is being developed based on coupling an Ensemble Monte Carlo simulation with a Finite Difference Time Domain electromagnetic simulation to model conductivity in both silicon and metals. In conjunction with this computational simulation, a method to conduct conductivity measurements in the near terahertz regime in the lab has been developed. The high quality factor (Q) resonant cavity will confirm the results of the computational simulation, as well as working independently to measure any other items of interest.